Who are the young users of tobacco products? Prevalence and characteristics of Danish adolescents who have either smoked cigarettes, used alternative tobacco products, or used both. Issue 6 (December 2021) - Kjeld, Simone Gad; Andersen, Susan; Andersen, Anette; Glenstrup, Stine; Lund, Lisbeth; Danielsen, Dina; Bast, Lotus Sofie
Aims: We examined characteristics (smoking in social relations, binge drinking, and well-being measures) of Danish 13-year-olds in relation to their tobacco use patterns. Ever use of cigarettes exclusively, ever use of alternative tobacco products (ATPs; e-cigarettes, snus, or waterpipe) exclusively, and use of both cigarettes and ATPs were studied. Methods: We used self-reported data from students at 46 Danish schools in 2017 comprising 2, 307 students (response rate = 86%). Multi-level logistic regression analyses were used to examine the associations between student characteristics and the odds for having ever used any tobacco products, smoked cigarettes exclusively, used ATPs exclusively, or used both cigarettes and ATPs compared with never use of any tobacco products. Unadjusted estimates and estimates adjusted for gender were reported. Results: A significant minority of youth (13.2%) had used one or more tobacco products. Of these, 2.0% had exclusively smoked cigarettes, 7.2% had exclusively used ATPs, and 4.0% had used both. Findings showed that all included characteristics (families' and friends' smoking, binge drinking, and well-being characteristics) were associated with using any tobacco product; however, students with friends who smoked, had been binge drinking, and had low well-being at home had notably higher odds for having both smoked cigarettes and used ATPs compared to the other tobacco use patterns. Conclusion: ATPs were popular among Danish adolescents compared with conventional cigarettes. Thus, prevention efforts among adolescents should not merely focus on the health risks of conventional cigarette smoking but also on ATPs. Students with diverse tobacco use patterns were similar on various characteristics. However, findings indicate that adolescents who had used both conventional cigarettes and ATPs constitute a more risk-averse group in special need of prevention efforts. Gender did not markedly influence the results. These findings may help future strategies aiming at the youngest adolescents at risk of using tobacco products.